2014
DOI: 10.1002/ange.201409270
|View full text |Cite
|
Sign up to set email alerts
|

Combining Topology and Sequence Design for the Discovery of Potent Antimicrobial Peptide Dendrimers against Multidrug‐Resistant Pseudomonas aeruginosa

Abstract: Multidrug‐resistant opportunistic bacteria, such as Pseudomonas aeruginosa, represent a major public health threat. Antimicrobial peptides (AMPs) and related peptidomimetic systems offer an attractive opportunity to control these pathogens. AMP dendrimers (AMPDs) with high activity against multidrug‐resistant clinical isolates of P. aeruginosa and Acinetobacter baumannii were now identified by a systematic survey of the peptide sequences within the branches of a distinct type of third‐generation peptide dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…We identified our first membrane disrupting antimicrobial peptide dendrimer (AMPD) by screening a combinatorial library using an off-bead Bacillus subtilis growth inhibition assay, [22 -24] which pointed to dendrimer bH1, a third generation (G3) dendrimer containing single hydrophobic residues in its branches and eight positive charges at the N-termini ( Figure 1, Table 1). [25,26] We then exploited multivalency and sequence design to obtain AMPD G3KL, [27] a G3 dendrimer featuring a lysine-leucine (KL) dipeptide in its G0, G1, G2, and G3 branches, a sequence element frequently encountered in linear antimicrobial peptides (AMPs). [28][29][30][31][32] Compared to our original AMPD bH1, extending single amino acid branches to dipeptides in all generations increased the number of positive charges and hydrophobic groups as means to confer stronger antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…We identified our first membrane disrupting antimicrobial peptide dendrimer (AMPD) by screening a combinatorial library using an off-bead Bacillus subtilis growth inhibition assay, [22 -24] which pointed to dendrimer bH1, a third generation (G3) dendrimer containing single hydrophobic residues in its branches and eight positive charges at the N-termini ( Figure 1, Table 1). [25,26] We then exploited multivalency and sequence design to obtain AMPD G3KL, [27] a G3 dendrimer featuring a lysine-leucine (KL) dipeptide in its G0, G1, G2, and G3 branches, a sequence element frequently encountered in linear antimicrobial peptides (AMPs). [28][29][30][31][32] Compared to our original AMPD bH1, extending single amino acid branches to dipeptides in all generations increased the number of positive charges and hydrophobic groups as means to confer stronger antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…They kill microorganisms using various strategies that include membrane disruption as the chief mechanism, apart from having downstream intracellular targets (14). They offer themselves as attractive substitutes for conventional small molecule drugs in view of their membrane disruption properties that allow them to circumvent the development of resistance in microbial targets (3,(15)(16)(17)(18). A number of these naturally occurring molecules are endowed with antimicrobial activities; however, their use is restricted to topical applications owing to their cytotoxicity (19).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the combination of various topology and sequence designs allowed for the discovery of potent antimicrobial peptide dendrimers (AMPDs) against MDR P. aeruginosa 18 . Indeed, the activities of the AMPDs, namely G3KL and G3RL ( Fig.…”
mentioning
confidence: 99%